A clinical perspective of therapeutic drug monitoring of cyclosporine in pediatric patients with kidney transplant - Roganović, Maša; Jovanović, Marija; Vučićević, Katarina (Archives of Pharmacy, 2025)
Cyclosporine A (CsA) is an immunosuppressive used in both children and adult transplant recipients, as well as patients with autoimmune diseases such as nephrotic syndrome. Therapeutic drug monitoring (TDM) of CsA is essential due to its significant interindividual and intraindividual pharmacokinetic variability, narrow therapeutic index and the risk of organ rejection or autoimmune disease relapse at subtherapeutic levels, as well as the potential for serious adverse effects with overexposure. In pediatric patients, CsA pharmacokinetics can be significantly influenced by developmental physiological factors, necessitating even greater attention to TDM in this vulnerable population. This paper explores the key challenges associated with TDM in children, the clinical rationale for its use, clinical settings where it is applied and future perspectives, including the potential of model-informed precision dosing (MIPD).
Keywords: cyclosporine; children; therapeutic drug monitoring; transplantation